"Volkskultur": Aspekte einer kulturtheoretischen Debatte in Wissenschaft und Literatur, Wien/Prag 1884-1939 - König, Anna-Maria (2012)
This study investigates the conceptualizations of 'Talk-culture" from the late 19th century through to the 1930s. "Folk-culture" was broadly discussed in this period all over Europe (and Russia) and especially in science (Philologies, Folkloristics) and literature. More precisely, the thesis examines the debates held in the context of the Austrian-Hungarian Empire (Vienna and Prague) around the turn of the century. During this period of accelerating industrialization, commodification and separation of cultural spheres, a significant number of intellectuals and writers were interested in alternative forms of cultural production. As the hitherto disregarded 'Talk-cultures" provide different notions of the artwork and the artist, their interest in 'Talk-culture" and 'Talk-art" is part of the broader discussion of the societal status and function of art and literature at the turn of the twentieth century. Representing a vehicle for the analysis and reflection of current cultural developments, the theorization of folklore and other forms of folk-art seeks responses to the aforementioned processes conceived as culturally problematic. Part Istudies the emergence of 'Volkskunde' as a scientific discipline in Austria. Part IIanalyses the relations between German Philology in Prague and the German-speaking Jews in the Prague Circle,namely Oskar Baum, Max Brad, Franz Kafka and Felix Weltsch. Part 11/ deals with the Russian linguists and folklorists Roman Jakobson and Petr Bogatyrev who came to Prague in the 1920s and sought to develop, in cambining Russian and Western European theories, a new model of 'Talk culture".